Assessment of Psychological Risk Factors for Spontaneous Abortion at Maternity Wards in Baghdad City Hospitals - Sarah Hashim Mohammed1 , Rabea Mohsen Ali 2 (Institute of Medico-legal Publications Pvt Ltd, 2020)
Objectives: To assess the psychological risk factors for spontaneous abortion. Methods: A descriptiveAnalytical study has been conducted on Non- probability sample consisted of (160) women who are sufferingfrom spontaneous abortion in maternity wards from six hospitals at Al Rusafa, AlKarckh and Medical cityhealth directorate. Study has been implemented for the period of January 10th 2020 to March 10th 2020 . Aquestionnaire used as a tool of data collection , the study instrument consist of Risk Factors (psychological,depression and anxiety ). Descriptive and inferential statistical analysis are used to analyze the data. Results:The study results shows that (60.6%) of women suffering from stress and anxiety during current pregnancy.Only (1.9%) have depression, (8.1%) are reporting the presence of sad events during current pregnancy,(8.8%) are reporting presence of death during current pregnancy, (26.3%) are experiencing a family problem,(25.6%) are violated by their husbands, and (6.9%) are violated by their husband’s family. Conclusion: Themajority of women are experiencing mild depression during their pregnancy, and more than half of womenare experiencing moderate anxiety during their pregnancy.